“Songs of Ancient China” – A Myth of “The Other” Appropriated by an Emerging Sinology (Mongolian Journal of International Affairs, 2015)
Legendary Czech Sinologist Průšek was attached to the ideal world created by Mathesius. And as can be seen from the words of contemporary senior Sinologists, the power of Průšek’s translations had a universal appeal among Czech readers at that time, inspiring interest in Sinology. The poet Mathesius, and later the Sinologist Průšek, with his authority of a scholar and teacher, used Chinese poetry to build up the idea of China as a world that would be an alternative to their own imperfect reality. This vision was transmitted to Průšeks pupils and through the power of popularization, which was according to Průšekan integral part of the academic duties of each scholar, was spread all over the cultural public. This alternative imaginary world enabled them to immerse in a beautiful fairy-tale, yet at the same time a fairy-tale in which familiar things could be recognized and desired, a world for which it is worth living among all the tragedies and desperation of the lived reality.Mongolian Journal of International Affairs Vol.19 2014: 134-152